Unity as Prophetic Witness : W.A. Visser 't Hooft and the Shaping of Ecumenical Theology - Kinnamon, Michael (Shapers of ecumenical theology, 2018)
W.A. Visser 't Hooft, a minister in the Netherlands Reform Church, was a pivotal figure in the rise of the ecumenical movement. Under his leadership, the World Council of Churches, which represents all the worldÂs major Christian faiths except the Roman Catholic, grew from 147 denominations in forty countries to nearly 300 in ninety countries.